Following the Global Rejection: The Motives of Majelis Ulama Indonesia's Fatwas on Ahmadiyah - Fariz Alnizar; Fadlil Munawwar Manshur; Amir Ma'ruf (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2022)
This article examines the motives behind the decisions of the Majelis Ulama Indonesia (MUI), in 1980 and 2005, to issue fatwas condemning the Ahmadiyah. Using critical discourse analysis, this study reveals MUI’s motives behind its fatwas on the Ahmadiyah by drawing on the text and the context of the issuance of the fatwas. Underpinning MUI’s issuance of its fatwa on the Ahmadiyah Qadiyan in 1980 was the global rejection of the Ahmadiyah, particularly in Pakistan and Saudi Arabia. Meanwhile, MUI’s fatwa on the Ahmadiyah in 2005 was informed by an increased rejection of the Ahmadiyah in Indonesia, which was based on the Jalsa Salana Ahmadiyah meeting in 2005, in Parung, Bogor. In the fatwa’s dictum, MUI positions itself as the guardian of the Islamic creed. MUI’s choice of wording and language style in its fatwas demonstrates its desire to display its authority as a quasi-non-governmental organization.